The Utilization of Digital Device during Pandemic Era - T Fidowaty; R Prastamawati; F M Subekti; D Klarado; N P Dewi (Peneliti.net, 2021)
This study aims to determine the level of teenage smartphone consumption in the Covid-19 pandemic era. The method used in this research is a descriptive survey method. This research method is useful for taking samples from the population and using a questionnaire as a data collection tool. Furthermore, the questionnaire will be distributed to 100 respondents who are adolescents aged 15 to 18 years. The results showed that adolescents tended to be consumptive towards using smartphones because it was based on individual needs, and during the pandemic of Covid-19, everything was completely online. Based on the research results, it can be concluded that smartphones among teenagers tend to be consumptive because of necessity.